PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVIS DI KELAS IV SD - Afriani, Revi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research of background by study of PKN during the time still teacher centre on. Resulting result learn which is wanted not yet been reached. Target of research depict the make-up of result learn student at study of PKN by using approach of konstruktivis. Assessment data in the form of information about data and process result of obtained action from result of perception. Source of data is process study of PKN in class of IV SDN 10 Hilalang semester of I school year 2012 / 2013. Result of research of show planning, result and execution learn natural student of improvement. Kata Kunci: hasil belajar siswa; pendidikan kewarganegaraan (PKn); dan pendekatan konstruktivis.